Drainage basin committees' reports. - United States. National Resources Committee. Water Resources Committee.; New England Regional Planning Commission. ([Washington] U.S. Govt. Print. Off., 1937)
"These reports were drafted in the field . to assist the Water Resources Committee of the National Resources Committee in preparing the report 'Drainage basin problems and programs, 1937 revision' transmitted to the Congress by the President March 10, 1938." Vol. 1 has title: Report of the New England Regional Planning Commission. v. 1. New England basins.--v. 2. North Atlantic basins.--v. 3. Chesapeake Bay drainage basins.--v. 4. Carolina Coastal and Savannah basins.--v. 5. Southeastern basins.--v. 6. Peninsular Florida basins.--v. 7. Tennessee and Cumberland basins.--v. 8. Ohio basins.--v. 9. Upper Great Lakes basins.--v.10. Lower Great Lakes and St. Lawrence basins.--v. 11. Hudson Bay basins.--v. 12. Upper Mississippi basins.--v. 13. Upper and middle Missouri basins.--v. 14. Lower Missouri basins.--v. 15. Arkansas, Upper White and St. Francis basins.--v. 16. Red and Ouachita basins.--v. 17. Lower Mississippi basins.--v. 18. Western Gulf basins.--v. 19. Colorado basin.--v. 20. Great Basin.--v. 21. California basins.--v. 22. Pacific Northwest basins. Mode of access: Internet. Spec. Coll. Haynes copy of v.21: Part of a collection (Collection 1604). To page this item, use the collection record; to find the collection record, search the title: Collection of books from the John Randolph Haynes and Dora Haynes Foundation Library. Item is in box 113. Printed white wrappers.